RELACIÓN ENTRE INVERSIÓN EXTRANJERA DIRECTA, LIBERTAD ECONÓMICA Y EL PRODUCTO INTERNO BRUTO PARA 100 PAÍSES DEL MUNDO: UN ENFOQUE DE COINTEGRACIÓN Y CAUSALIDAD CON DATOS DE PANEL, PERIODO 1980-2016 - Salinas Azuero, Andrea Cecibel (2019)
In the last years, the world economy has advanced considerably, attributed to several economics, political and social factors, such as new alliances between countries that encourage the transfer of capital, technology, new productive linkages, as well as protection of human rights, improvements in social services, etc. Much of this has to do with the decisions made by governments, which can have a positive or negative impact depending on the country where they are applied. Therefore, the present investigation examines the relationship between direct foreign investment and economic freedom in economic for long term, short term, also the causality among using econometrics tolos. through database management such as: World Bank, Freedom House, Fraser Institute and Heritage Foundation according to income level. The results describe a stable short-term and long-term relationship between foreign direct investment, economic freedom and economic growth, but non-existence of causality among the variables. An implication of economic policy derived from this research is the emphasis that the government must make in generating and maintaining the availability of labor, a good macroeconomic and legal environment, reduction of trade barriers, also generating subsidies not only to attract foreign capital, but also educational subsidies, which could help the poor to reach a better quality in their education, this in order to be able to become small entrepreneurs that help to stimulate local economies in the long term.